Training Preservice Science Teachers to Teach Inclusively - Watts, Elizabeth (Innovations in Science Teacher Education, 2022)
The United Nations Convention on the Rights of Persons with Disabilities was adopted in 2006. Since its ratification, the educational landscape has rapidly changed because inclusion requires a radical restructuring of mainstream schooling. At the classroom level, adaptations must be made to course materials, teaching approaches, testing, and other aspects of classroom teaching to meet the needs of an increasingly heterogeneous student body. To prepare future teachers to meet the objectives set forth in the United Nations Convention on the Rights of Persons with Disabilities (2006), it is necessary to develop preservice course modules that specifically cultivate sensitivity toward students with disabilities and train preservice teachers in how to adapt their teaching to accommodate students with disabilities or chronic illnesses. This type of training is critically important for preservice science teachers. The idea of inclusive education can be particularly daunting because of the complexity of science topics and the variety of educational activities that would require adaptation (e.g., course materials, experiments, and excursions). This article outlines an online, project-oriented module that effectively increased preservice science teachers’ positive views on inclusion and their self-efficacy in terms of accommodating effectively.